HI A ASSOCIATION WITH CHILDHOOD ACUTE LYMPHOBLASTIC LEUKEMIA - MAHDI, BATOOL M.; Shareef, salalwa M. (Journal of the Faculty of Medicine Baghdad, 2005)
Summary:OBJECTIVE Many associations have been found between specific HLA antigens and increased susceptibility to various diseases . So we tried to associate class I and class II antigens with acute lymphoblastic leukemia . We also demonstrate the presence of antibodies in serum of acute lymphoblastic leukemic patients against HLA class I.DESIGN: Prospective study.SETTING: Tissue typing and histocompatibility center at Al- Karamah Teaching Hospital. PATIENTS AND METHOD: 70 acute lymphoblastic leukemia patients from pediatric hospitals. HLA ( human leukocyte antigens) typing done for them by serological method and cross matching and blood grouping were also done for them.RESULTS: there was significant difference between patients and control groups regarding HLA -C6.DR1, DR4, DR7, DQ1.DQ2 ,DQ3, DQ4. There was 14.2 % (10/70) of patients had antibodies against HLA class I. There was no significant association between blood group and acute lymphoblastic leukemia .CONCLUSION: Genetic factor increased susceptibility with acute lymphoblastic leukemia ( HLA- DR1 DQ1, HLA - DR4 DQ4, HLA- DR4 DQ3, HLA- DR7 DQ2. This HLA typing increased susceptibility to be affected with leukemia after infection.RECOMMEND A TION: HLA typing was done to acute lymphoblastic leukemic patients by molecular -DNA based method (PCR-SSP, RSCA) in addition to serological method.